2015
DOI: 10.1039/c4ob02482f
|View full text |Cite
|
Sign up to set email alerts
|

Developing principles for predicting ionic liquid effects on reaction outcome. The importance of the anion in controlling microscopic interactions

Abstract: A series of ionic liquids containing anions of differing coordination strength were investigated as solvents for the condensation reaction of an alkyl amine and an aromatic aldehyde. As predicted, the rate constant of the process was found to increase with the proportion of the ionic liquid in the reaction mixture. Temperature-dependent kinetic analyses demonstrated that by varying the ability of the anion to interact with the cation the magnitude of both the enthalpy and entropy of activation could be control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…For all substrates 2b and 2d-f as the amount of [Bmim][N(CF 3 SO 2 ) 2 ] 1 in the reaction mixture was increased there was a gradual increase in k 2,A , as expected (Table 4, Fig. 0.4, this has appeared many times in our previous work, 28,36,39 and the source of this decrease in the rate constant at a particular proportion of ionic liquid is still under investigation. 4 and S1 † for substrates 2f and 2b, respectively, where k 2,A was determined at a number of different values of χ IL ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…For all substrates 2b and 2d-f as the amount of [Bmim][N(CF 3 SO 2 ) 2 ] 1 in the reaction mixture was increased there was a gradual increase in k 2,A , as expected (Table 4, Fig. 0.4, this has appeared many times in our previous work, 28,36,39 and the source of this decrease in the rate constant at a particular proportion of ionic liquid is still under investigation. 4 and S1 † for substrates 2f and 2b, respectively, where k 2,A was determined at a number of different values of χ IL ).…”
Section: Resultssupporting
confidence: 74%
“…36,39 In those cases, the rate enhancement in the ionic liquid 1 was shown to be the result of an entropic benefit overcoming an enthalpic cost; this enthalpic cost corresponds to coordination and stabilisation of the nucleophile 3 by the cation of the ionic liquid (this can also be thought of as a decrease in the apparent nucleophilicity of hexan-1-amine 3 in [Bmim][N(CF 3 SO 2 ) 2 ] 1 relative to acetonitrile). 36,39 In those cases, the rate enhancement in the ionic liquid 1 was shown to be the result of an entropic benefit overcoming an enthalpic cost; this enthalpic cost corresponds to coordination and stabilisation of the nucleophile 3 by the cation of the ionic liquid (this can also be thought of as a decrease in the apparent nucleophilicity of hexan-1-amine 3 in [Bmim][N(CF 3 SO 2 ) 2 ] 1 relative to acetonitrile).…”
Section: Resultsmentioning
confidence: 99%
“…These data showed that with the ionic liquid 6 as the solvent (w 6 0.85) there was an increase in the enthalpy of activation accompanied by an increase in the entropy of activation relative to acetonitrile. 34,35 It was therefore of interest to determine whether this model could be extended to include other nucleophilic heteroatoms. The cause of this trend in the activation parameters was determined, through deconvolution studies and molecular dynamics simulations, to be an interaction between the nitrogen lone pair of pyridine 1 and the cation of the ionic liquid 6.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to note that these trends in the activation parameters are not observed in any bimolecular nucleophilic process involving a nitrogen nucleophile–,, and are only seen at a high mole fraction of the ionic liquid 2 ( χ 2 ≈0.7) for the equivalent reaction involving a phosphorus nucleophile ,. This suggests that proceeding down group 15 from phosphorus to arsenic‐based nucleophiles there is a ‘shift’ in the dominant ionic liquid solvent interaction for bimolecular nucleophilic substitution processes.…”
Section: Resultsmentioning
confidence: 98%
“…χ 2 ≈0.2. It is not unusual for the majority of the rate enhancement seen for bimolecular processes to occur after the addition of only a low proportion of the ionic liquid 2 to the reaction mixture with little change on subsequent addition; examples of note are the substitution processes and condensation reactions, involving a nitrogen nucleophile. This trend in the dependence of the rate constant on the amount of ionic liquid in the reaction mixture is different to the trends observed in the previous triphenylpnicogen study; whilst there is a slight decrease in the rate constant at χ 2 ≈0.4, the trend is not as marked as was the case for the phosphorus nucleophile 1 b at…”
Section: Resultsmentioning
confidence: 99%